The effect of mindfulness therapy through an android application on nurses' work stress: A literature review - Triyanto Triyanto; Ridlwan Kamaluddin (Alma Ata University Press, 2023)
Introduction: Several studies have shown that nurses have high levels of work stress. Work stress can be overcome with therapy, especially mindfulness therapy. The purpose of this literature review is to synthesize the literature on mindfulness therapy to reduce work stress for nurses.Objectives : The formulation of the problem in this study is how to influence mindfulness therapy through an android applicationon work stress on work nurses in Emergency Room.Methods: Literature search was carried out using several databases, including PubMed and Scient Direct. The keywords used are different in each database. For Pubmed use